Carol's Drawing - Carol Steinbeck:::Creator::::::::::::
A drawing done while Steinbeck and Carol were living with the Sheffields in Eagle Rock, Ca. The Lovejoys and others joined them not long after. This one is titled 'The Eagle Rock Self Expression Society's cross-country hurdle race [sic]'